Systematic Approach Revealed SERPING1 Splicing-Affecting Variants to be Highly Represented in the Czech National HAE Cohort - Grombirikova, Hana; Bily, Viktor; Soucek, Premysl; Kramarek, Michal; Hakl, Roman; Ballonova, Lucie; Ravcukova, Barbora; Ricna, Dita; Kozena, Karolina; Kratochvilova, Lucie; Sobotkova, Marta; Zachova, Radana; et al. (Journal of clinical immunology, 2023)
Hereditary angioedema due to C1 inhibitor deficiency (C1-INH-HAE) is a rare and life-threatening condition characterized by recurrent localized edema. We conducted a systematic screening of SERPING1 defects in a cohort of 207 Czech patients from 85 families with C1-INH-HAE. Our workflow involved a combined strategy of sequencing extended to UTR and deep intronic regions, advanced in silico prediction tools, and mRNA-based functional assays. This approach allowed us to detect a causal variant in all families except one and to identify a total of 56 different variants, including 5 novel variants that are likely to be causal. We further investigated the functional impact of two splicing variants, namely c.550 + 3A > C and c.686-7C > G using minigene assays and RT-PCR mRNA analysis. Notably, our cohort showed a considerably higher proportion of detected splicing variants compared to other central European populations and the LOVD database. Moreover, our findings revealed a significant association between HAE type 1 missense variants and a delayed HAE onset when compared to null variants. We also observed a significant correlation between the presence of the SERPING1 variant c.-21 T > C in the trans position to causal variants and the frequency of attacks per year, disease onset, as well as Clinical severity score. Overall, our study provides new insights into the genetic landscape of C1-INH-HAE in the Czech population, including the identification of novel variants and a better understanding of genotype-phenotype correlations. Our findings also highlight the importance of comprehensive screening strategies and functional analyses in improving the C1-INH-HAE diagnosis and management.
Keywords: inhibiční protein komplementu C1; RNA Splicing; sestřih RNA; RNA, Messenger; Humans; Česká republika; messenger RNA; lidé; hereditární angioedémy; Complement C1 Inhibitor Protein; Angioedemas, Hereditary; Czech Republic